2020
DOI: 10.11628/ksppe.2020.23.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Therapy Programs Enhancing Quality of Life and Reducing Depression and Burden for Caregivers of Elderly with Dementia

Abstract: Background and objective: The problem that follows the increase of dementia patients is the burden of caregivers caring for dementia patients. The purpose of this study was to examine the effects of horticultural therapy programs improving the quality of life and reducing the depression and burden of caregivers of the elderly with dementia. Methods: In this study, 19 caregivers of the elderly with dementia were selected, and the experiment was conducted by dividing the control group (n=9) and the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…To begin with, as a result of applying horticultural therapy to participants living in or going to senior care facilities that are similar to the group of participants in this study, it was found that horticultural therapy alleviated depression and solitude (Chen and Ji, 2015;Chan et al, 2017;Yoon and Sung, 2017). As a result of conducting horticultural therapy on caregivers of the elderly with dementia facing depression due to various problems such as severance of social relations, it was found that the therapy alleviated depression (Kim et al, 2020). Moreover, according to Kim and Park (2018) who conducted horticultural therapy on middle-aged women, the therapy reduced depression and anxiety of middle-aged women and also promoted their ego-identity.…”
Section: Introductionmentioning
confidence: 60%
“…To begin with, as a result of applying horticultural therapy to participants living in or going to senior care facilities that are similar to the group of participants in this study, it was found that horticultural therapy alleviated depression and solitude (Chen and Ji, 2015;Chan et al, 2017;Yoon and Sung, 2017). As a result of conducting horticultural therapy on caregivers of the elderly with dementia facing depression due to various problems such as severance of social relations, it was found that the therapy alleviated depression (Kim et al, 2020). Moreover, according to Kim and Park (2018) who conducted horticultural therapy on middle-aged women, the therapy reduced depression and anxiety of middle-aged women and also promoted their ego-identity.…”
Section: Introductionmentioning
confidence: 60%
“…GHT could potentially be useful for reducing inflammation and protecting neuronal functions in healthy elderly adults by reducing plasma IL-6 levels and maintaining plasma levels (Ng et al, 2018). Horticultural therapy program on patients with mild cognitive impairment and mild dementia showed an increase in life satisfaction and a decrease in depression (Kim et al, 2020).…”
Section: Restorative Gardensmentioning
confidence: 99%
“…For the bereaved, the garden healing program conducted twice a week for 10 sessions was effective in psychological improvement including depression, anxiety, and lethargy (Na, 2020). A review of 11 studies regarding the psychological and physiological effects of gardens reported that the garden environment had the effect of relieving physiological stress and improving negative psychological states (Kang et al, 2020).…”
Section: Korean Mental Health Assessmentmentioning
confidence: 99%
“…Studies of gardening and similar activities include: a systematic review of current research on the health benefits of a garden environment (Kang et al, 2020); a study on the effects of a horticultural therapy program focusing on gardening activities ; an analysis of the healing effects of forest therapy and horticultural therapy (Park et al, 2015); community gardening activities and their effects on mental health of residents (Jang et al, 2019). There has also been a study on the effect of garden healing programs on the psychological emotion of the bereaved (Na, 2020).…”
Section: Introductionmentioning
confidence: 99%